Physical Premotion and Human Freedom - Svoboda, David (Verbum – Analecta Neolatina, 2004)
The paper shows how two outstanding Thomists solved the problem of the Divine previous concursus in relation to human freedom. First, the paper explains what the Physical premotion according to Thomists is, and then it turns to the Thomistic definition of self-determination in order to follow the Thomistic explanation that the infallible outgoing of the act of willing is compatible with human freedom. The author tries to analyse some key Thomistic claims with the help of possible world semantics.